Long-term illness in children its effects on patterns of behavior of siblings and on family roles - Lorenzo, Florita D.
The family operates as a system. As such long-term illness in a child affects in some way other members of the family. A family-centered approach in health care requires understanding of the needs and problems brought about by the stress of long-term illness in a family. Purpose: 1. To determine the effects of long-term illness on the pattern of behavior of siblings in 3 areas, namely; 1) household activities, 2) school activities, and 3) social activities. 2. To determine the effects of long-term illness on family roles in 5 areas: 1) caretaking, 2) housekeeping, 3) provides-role related activities, 4) social activities, and 5) marriage role activities. 3. To determine factors which significantly influence changes in siblings' behavior and family roles. 4. To determine specific changes in siblings' behavior and family roles. 5. To determine reactions of siblings to the child's illness. Setting and Subjects: The pediatric wards and out-patient departments of 3 government-run hospitals and 1 private hospital in Metro Manila were used for the study. Mothers who watched their children in the hospital or brought their ill children to the clinic for follow-up care were interviewed. 57 mothers of cardiac patients and 43 mothers of neurologic patients were interviewed. For the siblings, 146 school age and adolescent (6-18 years old) brothers and sisters of these ill children were the subjects of this study. Findings: 1. After onset of a child's illness, there was a significant increase of siblings' household activities, and significant decrease in school and social activities, regardless of variables. 2. After onset of a child's illness, there was a significant decrease in family roles in four areas. 3. Variable which significantly influenced change in sibling's social activities after onset of illness of the child are age of siblings and type of illness; the other independent variables did not significantly influence change in siblings' behavior. 4. Variables which significantly influenced family roles after the onset of illness of the child are SES, place of residence, kinship support, and type of illness. 5. Descriptive analysis showed that: a. Siblings' school performance was associated with duration of illness. b. Girl siblings are delegated more caretaking activities than boy siblings. c. Peer-group activities are the most affected of the siblings' social activities. d. The number of work hours of husband did not change appreciably after illness, while those of working mothers considerably decreased. e. Satisfactory husband-wife relationships was not affected by illness; in 1 case, an unsatisfactory relationship improved after onset of child's illness.